Impacts of Earthquake Aftermath on Indoor Carbon Monoxide Levels in Turkish Coffeehouses Environment in Duzce, Turkey - Bahcebasi, T (Tehran University of Medical Sciences, 2012)
BACKGROUND: In 1999, Duzce suffered two consecutive devastating earthquakes above magnitude 7 in August and November. In the present study, we aimed to evaluate the indoor air quality of coffeehouses by determining carbon monoxide (CO) levels and their contributing factors in coffeehouses built before and after the earthquake. METHODS: We conducted our study in 76 Turkish coffeehouses in Duzce in winter (November 2007–March 2008) during rush hours (18:00–23:00). The Turkish coffeehouses included in the study were evaluated under four categories based on smoking status and construction date. The characteristics of the coffeehouses, such as their CO levels and temperatures both indoors and outdoors, were all measured. These analyses were carried out with the SPSS 15.0 program. RESULTS: The CO levels in Turkish coffeehouses were above the values indicated as being safe by the WHO. While stoves and cooking equipment were determined to contribute to indoor CO levels, cigarettes were found to be the main source. Indoor CO levels at second hour were very strongly correlated (r: 0.84, P<0.001) (r: 0.91, P<0.001) with indoor CO levels at initial and first hour as well as with smoking status (r: 0.69, P<0.001); they were also moderately correlated with the room volume (r: 0.34, P<0.001) and construction materials (r: 0.31, P<0.001) of the coffeehouse. CONCLUSION: Elevated CO levels in Turkish coffeehouses indicate the possible presence of other pollutants, particularly when the main source is smoking. In such cases, both individuals and the whole of society are affected negatively in many ways. Therefore, smoking should be prohibited by law in Turkish coffeehouses and national awareness programs should be developed based on peoples’ lifestyles. Moreover, the standards for construction and management of Turkish coffeehouses should be improved as well.